2003
DOI: 10.1007/s00464-002-9119-9
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ablation of Barrett's esophagus using argon plasma coagulation (APC) following surgical laparoscopic fundoplication

Abstract: The success rate of APC ablation following laparoscopic antireflux surgery in our series may be as high as 91%. Nevertheless, small islands of intestinal metaplasia under the new squamous epithelium may persist in some patients. In these circumstances, the authors recommend that endoscopic ablation of BE should be confined to controlled clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 13 publications
2
10
0
2
Order By: Relevance
“…In the published postsurgical APC ablation studies, the length of follow-up has been relatively short, with the mean duration of follow-up being 17 18 and 31.9 months. 19 Successful initial neosquamous re-epithelialization was achieved in more than 90% of patients in these studies, and similar outcomes have been reported for ablation using bipolar electrocoagulation 20 and endoscopic laser 21 in patients who had undergone a previous fundoplication.…”
Section: Discussionsupporting
confidence: 68%
“…In the published postsurgical APC ablation studies, the length of follow-up has been relatively short, with the mean duration of follow-up being 17 18 and 31.9 months. 19 Successful initial neosquamous re-epithelialization was achieved in more than 90% of patients in these studies, and similar outcomes have been reported for ablation using bipolar electrocoagulation 20 and endoscopic laser 21 in patients who had undergone a previous fundoplication.…”
Section: Discussionsupporting
confidence: 68%
“…The results of the present study suggest that relapse can be found more frequently in patients with the intestinal predominant mucin phenotype. However, several investigators have reported that relapse of Barrett’s mucosa derives from remnant Barrett’s epithelial cells underneath the newly developed squamous epithelium after endoscopic mucosal ablation 55–57 . In future studies, it will be necessary to elucidate the relationship between relapse of Barrett’s esophagus and the mucin phenotype of remaining Barrett’s mucosa in the subepithelial layer.…”
Section: Discussionmentioning
confidence: 99%
“…De allí surge la posibilidad de someter a estos pacientes a ablación con argón plasma por vía endoscópica para disminuir este riesgo de desarrollar un adenocarcinoma [1][2][3][4][5] . Recientemente se ha descrito la restauración parcial de la mucosa escamosa después de la ablación de EB con técnicas endoscópicas 6,7 .…”
Section: Seguimiento Endoscópico E Histológico Post Ablación Con Argóunclassified